Evaluating The Performance of Public Companies in The Light of Financial Indicators Case study of the General Company for Drugs and Medical Supplies/ Samarra – Iraq For the period (2014-2019) - Mohammed, Thulfiqar Abdul Majeed; Altaee, Ali Hasson (Journal of Economics and Administrative Sciences, 2021)
The research aimed to evaluate the financial performance of the Public Company for the manufacture of medicines and medical supplies / Samarra - Iraq to know the strengths and weaknesses that affect its performance, as well as to compare its performance in the years between (2017-2019), which are characterized by security stability with its performance in previous years (2014 -2016) which is characterized by security instability, to assess the extent of its ability to achieve growth in performance, by answering the main question, what is the evaluation of the performance of the Public Company for the manufacture of medicines and medical supplies / Samarra - Iraq in the light of financial indicators?To reach an answer to this question and achieve the goal of the research, a methodology (case study) was adopted to address the problem at hand and rely on financial analysis indicators to analyse the financial statements of the company for research sample represented by (Balance sheet and the income statement) during the period (2014-2019). And the research reached a set of results, the most important that is can be evaluated the performance of (Public Company for Medicines and Medical Supplies / Samarra - Iraq)  by relying on financial indicators represented by (liquidity indicators, indebtedness indicators, activity indicators and profitability indicators), and that there is a decrease in the company's performance, Which is sometimes due to the impact of the security situation and instability, and although there is a slight growth in its performance, it is far from the level of ambition. and Given the challenges faced by public companies in Iraq, the search variables are of great value to Iraqi public companies in general and to The company of sample research in particular